Review: Marine Seismic And Side-Scan Sonar Investigations For Seabed Identification With Sonar System - Lubis, Muhammad Zainuddin; Anggraini, Kasih; Kausarian, Husnul; Pujiyati, Sri (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Marine seismic reflection data have been collected for decades and since the mid-to late- 1980s much of this data is positioned relatively accurately. Marine geophysical acquisition of data is a very expensive process with the rates regularly ship through dozens of thousands of euros per day. Acquisition of seismic profiles has the position is determined by a DGPS system and navigation is performed by Hypack and Maxview software that also gives all the offsets for the equipment employed in the survey. Examples of some projects will be described in terms of the project goals and the geophysical equipment selected for each survey and specific geophysical systems according to with the scope of work. For amplitude side scan sonar image, and in the multi-frequency system, color, becoming a significant properties of the sea floor, the effect of which is a bully needs to be fixed. The main confounding effect is due to absorption of water; geometric spread; shape beam sonar function (combined transmit-receive sonar beam intensity as a function of tilt angle obtained in this sonar reference frame); sonar vehicle roll; form and function of the seabed backscatter (proportion incident on the seabed backscattered signal to sonar as a function of the angle of incidence relative to the sea floor); and the slope of the seabed. The different angles of view are generated by the translation of the sonar, because of the discrete steps involved by the sequential pings, the angular sampling of the bottom.